2012
DOI: 10.1073/pnas.1217018109
|View full text |Cite
|
Sign up to set email alerts
|

Calaxin drives sperm chemotaxis by Ca 2+ -mediated direct modulation of a dynein motor

Abstract: ] i ) in sperm significantly alters swimming direction during chemotaxis (3, 4). Recent studies of human sperm suggest that progesteronemediated Ca 2+ influx through a Ca 2+ channel, CatSper, plays essential role in motility changes, such as hyperactivation and chemotaxis (5, 6), although both phenomena are argued to be separated (7). However, Ca 2+ is a primary factor regulating symmetry of flagellar waveform (8, 9). Chemotactic movements are achieved by continuous changes in waveform symmetry of sperm flagel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 83 publications
(98 citation statements)
references
References 25 publications
4
93
1
Order By: Relevance
“…However, the basic structures of the flagellar axoneme are conserved among these animals. Interestingly, a study reported the details of the sliding of dynein motor‐driven microtubules in the flagellar axoneme during the sperm chemotaxis of marine animals 25. In order to elucidate the swimming direction‐changing mechanism of chemotactic bull sperm, information on the dynamics of the structural elements of the sperm flagellar axoneme might be useful.…”
Section: Discussionmentioning
confidence: 99%
“…However, the basic structures of the flagellar axoneme are conserved among these animals. Interestingly, a study reported the details of the sliding of dynein motor‐driven microtubules in the flagellar axoneme during the sperm chemotaxis of marine animals 25. In order to elucidate the swimming direction‐changing mechanism of chemotactic bull sperm, information on the dynamics of the structural elements of the sperm flagellar axoneme might be useful.…”
Section: Discussionmentioning
confidence: 99%
“…The maintenance and regulation of intracellular calcium concentration ([Ca 2+ ] i ), is therefore, of great importance and is carried out by proteins and co-factors that import, export and/or sequester calcium ions [50]. In spermatozoa, swimming behavior is controlled by rises in [Ca 2+ ] i that changes flagellar beat pattern through Ca 2+ sensing proteins calaxins [51,52]. Calciumbound calaxins inhibit the activity of dynein motors within the Murine potassium channel KSper comprised of the Slo3 channel and associated gamma subunit LRRC52, as well as possible beta subunits.…”
Section: Calcium Channels and Hyperactivationmentioning
confidence: 99%
“…The OAD from animal sperm has two HCs, two WD-repeat ICs, a unique IC with thioredoxin and nucleoside diphosphate kinase domains [30][31][32], and regulatory LCs such as Tctex-2 LC [33,34] and a Ca 2? -binding protein named calaxin [35][36][37] (Fig. 1d).…”
Section: Structure Of the Axonemementioning
confidence: 99%
“…OAD is involved in the elevation of ciliary beat frequency [19], force generation for penetration of sperm through the zona pellucida [141], metachronal synchrony of motile cilia [142], and propagation of asymmetric waveforms of sperm during chemotaxis [36]. The mutations in OAD reported so far include those in HCs (DNAH5, DNAH11), ICs (DNAI1, DNAI2, NME8), a LC (DNAL1), and a component of the DC (coiled-coil domain containing protein 114, CCDC114; DC2 in Chlamydomonas) ( Table 1).…”
Section: Oda and Idamentioning
confidence: 99%